The interest of Grade IV, V, and VI Students in Playing Football at Sarroanging Inpres Elementary School, Bungaya District, Gowa Regency - Saleh, Muhammad Syahrul; Saleh, M. Sahib (UNIVERSITAS NEGERI MAKASSAR, 2024)
Interest is one element that plays an important role in making a decision. The data collection method in this study used a survey method with data collection techniques using questionnaires. Questionnaires are divided into two types, namely closed questionnaires and open questionnaires. In this study, the authors chose a closed questionnaire as an instrument for collecting research data. The results of this study were a study of students' interest in playing football, the data was disclosed using a questionnaire consisting of internal factors including interest, attention, and activity, and external factors including family, school, and environment. Data were analyzed using percentage descriptions presented in the form of tables and diagrams using a Likert scale with five alternative answers, namely: strongly agree (SS), agree (S), Doubtful (R), disagree (TS), and Strongly disagree (STS). The results of this study reveal what things are indicators of student interest in playing football, internal factors, namely the first: An indicator of interest in which students' interest in playing football if measured from a Likert scale, the most chosen is (SS ). and the lowest is (STS) with a percentage of 9%. Furthermore, external or external factors, namely: the highest family indicator (S) with a percentage of 29% and the lowest (STS) 7%, the most chosen school indicator (S) with a percentage of 35%, and the lowest is ( STS) 7%, the most chosen Environmental Indicator is (S) with a percentage of 31% and the lowest (STS) 10%.